Efeitos da Violaceína sobre as formas evolutivas de Trypanosoma cruzi - Canuto, Jader Almeida (2016)
The World Health Organization estimates that about 7 to 8 million people are infected with Trypanosoma cruzi in the world. Treatment of Chagas disease has limited efficacy and side effects that limit tolerability and patient compliance. The search for new therapeutic alternatives from bioactive substances has grown significantly in recent years. Violacein (VIO), a bacterial pigment produced by Chromobacterium violaceum has shown several biological actions, among them, antiulcer action, antitumor, antiviral, and antiparasitic. In this paper, we studied the effects of VIO on the evolutionary forms of Trypanosoma cruzi. Epimastigotes were cultured in LIT at 28 ° C in the presence of VIO (0.97; 1.9; 3.9; 7.8; 15.62; 31.25; 62.5; 125; 250 ; 500; 1000μM) for 24, 48 and 72 hours. The trypomastigotes were obtained after infection in LLC-MK2 cells resuspended in DMEM 2% FBS and incubated with VIO (0.97; 1.9; 3.9; 7.8; 15.62; 31,25μM ) for 24h. amastigotes were cultivated on circular coverslips within culture plates containing LLC-MK2 cells and treated with violacein (4.97 and 9.94 mM). Cytotoxicity on LLC-MK2 mammalian cells was assessed using the MTT reduction assay, after incubation with VIO (3.9; 7.8; 15.62; 31.25; 62.5; 125; 250; 500μM ) for 24h. The evaluation of the process of cell death was made from the marking epimastigotes with 7AAD and Annexin V-PE after treatment with VIO (51.39 and 102,78μM). To determine the production of reactive oxygen species, epimastigotes were incubated with VIO (51.39 and 102,78μM). In determining the effect on the mitochondrial membrane potential, it was used Rhodamine 123 marker in epimastigotes treated with VIO (102,78μM). In epimastigotes, the substance showed trypanocidal action, with IC50 value of 51.39; 104.7 67,78μM and 24, 48 and 72h of treatment, respectively. In trypomastigotes, the IC 50 was 4,97μM in 24 hours. The analysis of amastigotes reduced the percentage of infected cells and the survival rate of these, at 24 and 48 hours at concentrations of 4.97 and 9.94 uM. In determining the cytotoxic effect on LLC-MK2, there was obtained an IC50 of 47,91μM. The analysis of the mechanisms of cell death allowed to infer that the VIO cause death in parasites predominantly by apoptosis. It was observed the production of reactive oxygen species (ROS), which can contribute to the aforementioned type of death. It was also observed a reduction in the mitochondrial membrane potential in the treated groups. All experiments were performed in triplicate (n = 3). For comparison of the experimental groups, the ANOVA was used, with post-test Dunnett, using p <0.05 as significance criterion. Thus, VIO presented trypanocidal effects on all of the evolutionary cycle of the parasite forms, suggesting involvement of reactive oxygen species and changes in mitochondrial membrane potential in the process of cell death by apoptosis.